2022
DOI: 10.4103/2045-9912.325991
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Iranian Polyherbal Syrup (Zufa syrup) on oxygen saturation and clinical symptoms in suspected patients with COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) pandemic has caused an urgent need for investigating potential treatments. Traditional medicine offers many potential remedies that have been historically used and have the advantage of bypassing the cultural obstacles in the practice of medicine. We aimed to investigate the efficacy of Zufa syrup in the treatment of suspected patients with mild to moderate symptoms of COVID-19. This triple-blind randomized controlled trial recruited patients with evidence of COVID-19 on che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…One study used Viola odorata L. aqueous extract (violet syrup) [36]; one study used pomegranate juice added to SUMAC (a composition of tannins, flavonoids, anthocyanins, isoflavones, terpenoids, and diterpenes) [37]; one study used Covexir (Ferula foetida oleogum) [38]; one study used Zufa syrup (a composition of Nepeta bracteata, Ziziphus jujube, Glycyrrhizaglabra, Ficuscarica, Cordia myxa, Papaver somniferum, Fennel, Adiantumcapillus veneris, Viola, Viper's-buglosses, Lavender, and Iris) [39]; one study used sachets of Matricaria chamomilla L., Zataria multiflora Boiss., Glycyrrhiza glabra L., Ziziphus jujuba Mill., Ficus carica L., Urtica dioica L., Althaea officinalis L., Nepeta bracteata Benth, and capsules of Rheum palmatum L. rizhome, Glycyrrhiza glabra root, Punica granatum L. fruit peel, Rheum palmatum, and Nigella sativa L. [40]; one study used giloy, swasari ras, ashwagandha, and tulsi ghanvati [41]; one used a multicomponent over-the-counter formulation [42]; one used lacto-wolfberry [43]; one used aged garlic extract powder [44]; one used ephedra herb, apricot kernel, cinnamon bark and glycyrrhiza root [45]; one used ginseng [46]; two used broccoli sprout decoction [47,48]; one used a Chima qingwen decoction [49]; one used elderberry extract orally [50]; and one use posaconazole [51]. The administered doses ranged from 300 mg to 200 g per day, and the intervention period ranged from 4 days to 20 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study used Viola odorata L. aqueous extract (violet syrup) [36]; one study used pomegranate juice added to SUMAC (a composition of tannins, flavonoids, anthocyanins, isoflavones, terpenoids, and diterpenes) [37]; one study used Covexir (Ferula foetida oleogum) [38]; one study used Zufa syrup (a composition of Nepeta bracteata, Ziziphus jujube, Glycyrrhizaglabra, Ficuscarica, Cordia myxa, Papaver somniferum, Fennel, Adiantumcapillus veneris, Viola, Viper's-buglosses, Lavender, and Iris) [39]; one study used sachets of Matricaria chamomilla L., Zataria multiflora Boiss., Glycyrrhiza glabra L., Ziziphus jujuba Mill., Ficus carica L., Urtica dioica L., Althaea officinalis L., Nepeta bracteata Benth, and capsules of Rheum palmatum L. rizhome, Glycyrrhiza glabra root, Punica granatum L. fruit peel, Rheum palmatum, and Nigella sativa L. [40]; one study used giloy, swasari ras, ashwagandha, and tulsi ghanvati [41]; one used a multicomponent over-the-counter formulation [42]; one used lacto-wolfberry [43]; one used aged garlic extract powder [44]; one used ephedra herb, apricot kernel, cinnamon bark and glycyrrhiza root [45]; one used ginseng [46]; two used broccoli sprout decoction [47,48]; one used a Chima qingwen decoction [49]; one used elderberry extract orally [50]; and one use posaconazole [51]. The administered doses ranged from 300 mg to 200 g per day, and the intervention period ranged from 4 days to 20 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Borujerdi et al [39] conducted a placebo-controlled, randomized, triple-blind clinical trial to evaluate the effects of Zufa syrup (Nepeta bracteata, Ziziphus jujube, Glycyr-rhizaglabra, Ficuscarica, Cordia myxa, Papaver somniferum, Fennel, Adiantumcapillus ven-eris, Viola, Viper'sbuglosses, Lavender, and Iris) in reducing COVID-19 symptomatology. The results showed that the intervention was not significantly different from the placebo and did not exert treatment effects.…”
Section: Medicinal Plants Covid-19 and Influenzamentioning
confidence: 99%
“…This may be owing to the expectorant action of Pimpinella anisum, a CCOGA ingredient [10]. Other research on a polyherbal remedy did not nd any differences in SpO2 between the treatment group and the control group, so the CCOGA may be more effective [39].…”
Section: Discussionmentioning
confidence: 97%
“…CRP is a key pro-in ammatory marker that rises dramatically in severe COVID-19 patients and falls as the patient heals [38][39][40][41]. The use of CCOGA decreased the CRP level in the treatment arm as compared to the control arm.…”
Section: Discussionmentioning
confidence: 99%